The Role of Tumour Metabolism in Cisplatin Resistance - Wang, Lude; Zhao, Xiaoya; Fu, Jianfei; Xu, Wenxia; Yuan, Jianlie (Frontiers in Molecular Biosciences, 2021)
Cisplatin is a chemotherapy drug commonly used in cancer treatment. Tumour cells are more sensitive to cisplatin than normal cells. Cisplatin exerts an antitumour effect by interfering with DNA replication and transcription processes. However, the drug-resistance properties of tumour cells often cause loss of cisplatin efficacy and failure of chemotherapy, leading to tumour progression. Owing to the large amounts of energy and compounds required by tumour cells, metabolic reprogramming plays an important part in the occurrence and development of tumours. The interplay between DNA damage repair and metabolism also has an effect on cisplatin resistance; the molecular changes to glucose metabolism, amino acid metabolism, lipid metabolism, and other metabolic pathways affect the cisplatin resistance of tumour cells. Here, we review the mechanism of action of cisplatin, the mechanism of resistance to cisplatin, the role of metabolic remodelling in tumorigenesis and development, and the effects of common metabolic pathways on cisplatin resistance.